Implikasi Hukum Sistem Publikasi Pendaftaran Tanah Negatif Bertendensi Positif dalam Kasus Penerbitan Sertifikat Hak Milik yang Berasal dari Pewaris kepada Salah Satu Ahli Waris Tanpa Persetujuan Ahli Waris Lainnya - Fathia Qanita Erwin; Hasim Purba; Rosnidar Sembiring (Jurnal Hukum Lex Generalis, 2025)
The negative tendency positive land registration publication system in Indonesia, although designed to provide legal certainty, can in practice be misused by irresponsible individuals for personal gain while ignoring the rights of legitimate heirs. This creates legal uncertainty and harms parties who should be protected by the land registration system. The method used in this research is normative juridical research method, which refers to legal norms. The legal implications of issuing property certificates without heir consent in the negative tendency positive land registration system can lead to prolonged legal disputes, uncertainty in land ownership status, financial losses for heirs whose rights are violated, and can harm third parties acting in good faith, as occurred in the Supreme Court Decision No. 1404 K/Pdt/2019 case which created legal uncertainty and cascading losses for various parties.